A Human Rights-based Approach to Internal Displacement in the Context of Disasters and Climate Change. (7th January 2021) - Scott, Matthew; Salamanca, Albert
Abstract: This article argues that integrating displacement considerations into (sub-) national legal and policy frameworks relating to disaster risk reduction and management (DRRM) and climate change adaptation (CCA) can play an important role in preventing and preparing for displacement, protecting people during evacuation and throughout displacement, and facilitating durable solutions in the context of disasters and climate change. The manner in which displacement considerations are integrated, including in particular the extent to which human rights-based international standards and guidelines are incorporated, combined with the level of human and financial resources devoted to this issue, can affect implementation at the sub-national level. Ultimately, however, addressing internal displacement in this context is a matter of sustainable development, with DRRM focusing mostly on symptoms, rather than underlying structural causes. The argument is developed with reference to recently completed collaborative research focusing on law, policy, and practice relating to internal displacement in the context of disasters and climate change in 10 countries across Asia and the Pacific. It includes recommendations for further research.